Mass Transfer during Atmospheric and Vacuum Frying of Chorizo - Piedad Margarita Montero Castillo; Lesly Torres Díaz; Sandy Torres Díaz; Diofanor Acevedo Correa; Raúl J. Martelo Gómez (International Journal of Food Science)
The main objective of this study was to evaluate the kinetics of moisture and oil uptake during chorizo deep-fat frying as compared to atmospheric and vacuum conditions. The conditions in the process were 90, 120, and 150°C for vacuum frying and 160, 170, and 180°C for atmospheric frying. The kinetics of moisture loss during atmospheric and vacuum frying was studied from the analytical solution of Fick’s second law for cylinder geometry. Oil absorption was also determined using a first-order kinetic model. The moisture content decreased by 33.72% at the maximum process temperature and time during vacuum frying (150°C, 360 s), as compared to the atmospheric frying, which was 28.61% (180°C). The oil content at the end of the process (360 s) was 27.79% (90°C), 27.31% (120°C), and 24.82% (150°C) for vacuum-fried chorizos, and higher values were obtained in the atmospheric frying, obtaining values of 34.45% (160°C), 31.36% (170°C), and 28.47% (180°C) (p<0.05). In summary, the vacuum frying yielded sausages with a lower final oil percentage and higher moisture content; these results are promising because they may influence consumer preference for sensory parameters.